The Association of Pre-Transplant C-Peptide Level with the Development of Post-Transplant Diabetes: A Cohort Study. Issue 10 (27th October 2022) - Vinson, Amanda J.; Thanamayooran, Aran; Kiberd, Bryce A.; West, Kenneth; Siddiqi, Ferhan S.; Gunaratnam, Lakshman; Tennankore, Karthik K.
Key Points: A pretransplant fasting C-peptide level ≥3000 pmol/L was associated with a nearly 20-fold increased odds of post-transplant diabetes mellitus at 1 year post kidney transplantation. In a restricted cohort with a body mass index between 20 and 35 kg/m 2, a pretransplant C-peptide ≥3000 pmol/L was the only factor independently associated with post-transplant diabetes mellitus. Hemoglobin A1c at 1 year post kidney transplant was significantly higher (5.9% versus 5.5%, [ P =0.02]) in those with a high versus low pretransplant C-peptide levels. Visual Abstract: Abstract : Background: Post-transplant diabetes mellitus (PTDM) is an important complication after kidney transplantation that results in reduced patient and allograft survival. Although there are established risk factors for PTDM, whether pretransplant C-peptide levels associate with PTDM is unknown. Therefore, in this study, we aimed to examine the association of pretransplant C-peptide levels with PTDM. Methods: This was a cohort study of nondiabetic adult patients who underwent kidney transplant in Nova Scotia, Canada, between January 1, 2016, and March 31, 2021, with fasting C-peptide levels measured before transplant. Multivariable logistic regression was used to determine the association of pretransplant C-peptide (dichotomized around the median) with PTDM at 1 year post transplant. Given the known association between pretransplant obesity and PTDM, we repeated our primary analysis in a cohort restricted to a BMI of 20–35 kg/m 2 . Results: The median C-peptide value was 3251 (Q1 2480, Q3 4724); pretransplant C-peptide level was dichotomized at 3000 pmol/L. PTDM occurred in 25 (19%) individuals. Thirty percent of patients in the high and only 2% of patients in the low C-peptide groups developed PTDM ( P <0.001). A C-peptide level ≥3000 pmol/L was strongly associated with PTDM in multivariable analysis (OR=18.9, 95% CI, 2.06 to 174.2). In a restricted cohort with a BMI of 20–35 kg/m 2, an elevated pretransplant C-peptide remained independently associated with the risk of PTDM (OR=15.7, 95% CI, 1.64 to 150.3). C-peptide was the only factor independently associated with PTDM in this restricted BMI cohort. Conclusions: A pretransplant C-peptide level ≥3000 pmol/L was associated with a nearly 20-fold increased odds of PTDM at 1 year post kidney transplantation. Identifying patients with high pretransplant C-peptide levels may therefore help identify those at risk for PTDM who may benefit from focused preventative and therapeutic interventions and support.